2004
DOI: 10.1124/mol.104.007724
|View full text |Cite
|
Sign up to set email alerts
|

RGS2 Is a Mediator of Nitric Oxide Action on Blood Pressure and Vasoconstrictor Signaling

Abstract: The nitric oxide (NO)-cGMP pathway regulates vascular tone and blood pressure by mechanisms that are incompletely understood. RGS2, a GTPase-activating protein for Gq␣ that is critical for blood pressure homeostasis, has been suggested to serve as an effector of the NO-cGMP pathway that promotes vascular relaxation based on studies of aortic rings in vitro. To test this hypothesis and its relevance to blood pressure control, we determined whether RGS2 functions as an NO effector in smooth muscle of the resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…18,20,27 Additionally, it has been suggested that RGS2 may act as a downstream effector of the NO-cGMP pathway, resulting in vascular relaxation by attenuating vasoconstrictor signaling, whereas suppression of this mechanism may facilitate development of hypertension. 25 In this context, Semplicini et al demonstrated an association between the rs4606 G allele and RGS2 expression in peripheral blood mononuclear cells in hypertensive patients, with the lowest values in GG homozygotes. 20 In a smaller number of subjects from the same study (cases and controls), RGS2 gene and protein expression were also reduced in fibroblasts from those carrying either the CG or GG genotype.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…18,20,27 Additionally, it has been suggested that RGS2 may act as a downstream effector of the NO-cGMP pathway, resulting in vascular relaxation by attenuating vasoconstrictor signaling, whereas suppression of this mechanism may facilitate development of hypertension. 25 In this context, Semplicini et al demonstrated an association between the rs4606 G allele and RGS2 expression in peripheral blood mononuclear cells in hypertensive patients, with the lowest values in GG homozygotes. 20 In a smaller number of subjects from the same study (cases and controls), RGS2 gene and protein expression were also reduced in fibroblasts from those carrying either the CG or GG genotype.…”
Section: Discussionmentioning
confidence: 98%
“…As with the majority of vasoconstrictors, Ang II signals via G proteincoupled receptors that are coupled to G q protein to increase intracellular calcium and subsequent responses, such as vasoconstriction. 3,25 Ang II may also exert some of its effects via G i protein signaling. 26 RGS2 acts as a GTPase activating protein, negatively regulating both G q/11 as well as G i/o proteins by enhancing the termination of the activated G protein state.…”
Section: Discussionmentioning
confidence: 99%
“…3 In RGS2 knockout mice, the two pathways are disrupted and a strong hypertensive phenotype is observed. [3][4][5] In addition, our group and Riddle's group have recently reported that polymorphisms of human RGS2 are associated with human hypertension in a Japanese general population and in American blacks. 6,7 Just recently, other Japanese group reported that the polymorphism of near RGS2 is also associated with the development of hypertension evaluated by home blood pressure measuring.…”
Section: Introductionmentioning
confidence: 93%
“…RGS2 is one of the predominant RGS proteins in the cardiovascular system and has been shown to be crucial in the regulation of vascular tone and blood pressure. RGS2 deficiency in mice is associated with a hypertensive phenotype and an increased sensitivity, as well as prolonged responsiveness to vasoconstrictors (4)(5)(6). In addition, genetic polymorphisms of RGS2 are correlated with hypertension and intima-media thickening of carotid arteries in humans (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%